(untitled) (Research, Society and Development, 2020)
A movement for our dietary patterns in the last decades in various populations with an increase in the consumption of snacks and soft drinks. The research aimed to evaluate the consumption of ultra-processed foods and the consequences that these products have on the health of individuals. The search for articles was performed in electronic databases accessed through the Virtual Health Library (VHL), Medical Literature Analysis and Retrieval System online (MEDLINE), Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMED) and Science Direct, being used as inclusion criteria studies published in English and Portuguese published in the period from 2015 to 2020 and as exclusion criteria those who had issues that differed from the objective and that did not focus on the evaluation of food consumption, in addition to incomplete articles, reviews of literature, conference abstracts, dissertations, theses, editorials and letters. In all, a total of 138 articles from these 15 were carefully selected to compose the review. Studies on eating snacks and skipping meals are challenging and inconclusive, with many studies showing a relationship between the consumption of snacks and the increase in pathologies. Finally Even though these factors may be associated with inadequate food choices in some populations, the motivation for snacks, as well as the impact of snacks on health, are subject to considerable inter-individual variation, which merits further investigation.